Cerebroprotective effect of sitagliptin and aminoguanidine combination in disorders of cerebral circulation - D. V. Kurkin; D. A. Bakulin; E. I. Morkovin; Yu. V. Gorbunova; A. V. Strygin; T. M. Andriashvili; A. A. Sokolova; N. S. Bolokhov; V. E. Pustynnikov; E. A. Fomichev; A. V. Baskova; S. S. Polodyants; et al. (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2023)
The aim of the study was to evaluate a cerebroprotective activity of the sitagliptin and aminoguanidine combination in rats with an acute and chronic cerebral circulation insufficiency, as well as with a traumatic brain injury.Materials and methods. The study was carried out on male Wistar rats in 3 stages using, respectively, a model of a chronic pathology: a chronic cerebral circulation insufficiency (CCCI), as well as 2 models of the acute brain injury (BI): an acute cerebral circulation insufficiency (ACCI), and a traumatic brain injury (TBI). А CCCI was modeled by a bilateral stenosis of the common carotid arteries (by 50%), a model of a hemorrhagic stroke caused by an intracerebral injection of the autologous blood was used as a stroke, a TBI was modeled by a mechanical damage to the brain tissue. To assess the pathology course severity, the following tests were used: Adhesion test, Open field, Morris water maze test, as well as Garcia and Combs&D'Alecy scales. In the animals with an acute damage to the brain at the end of the experiment, the severity of edema of the affected hemisphere was also determined. The treatment was with sitagliptin (10 mg/kg), aminoguanidine (25 mg/kg), or a combination thereof. The obtained data were subjected to the statistical processing.Results. In the course of the study, it was found out that the administration of a sitagliptin and aminoguanidine combination, unlike each of the components, had a cerebroprotective effect in the animals with a chronic or acute damage to the brain, reducing the severity of psychoneurological (cognitive and sensory-motor) disorders, as well as the brain edema.Conclusion. Aminoguanidine, as an iNOS blocker, enhances the action of sitagliptin, preventing the brain edema development and reducing the neurological deficit severity (the severity of cognitive and sensory-motor impairments) in the animals with an acute and chronic cerebral circulation insufficiency.